Monitoring Akses Web Server Dengan Menggunakan Fiture Netwatch V7 Tcp-Conn MikrotikOs - Ahmad Fauzi; Andry Maulana (Jurnal Edik Informatika Penelitian Bidang Komputer Sains dan Pendidikan Informatika, 2023)
Internet access is an important thing for the running of an office activity where it is necessary to monitor access to the internet on a computer network, for that we need tools that can be utilized as monitoring internet access by using the Netwatch feature, Netwatch is one of the features owned by MikroTik which functions to monitor computer networks under host conditions at certain intervals. The way the Netwatch feature works is by periodically sending ICMP messages to the intended host, and we can add scripts or information based on the results of checking whether the ICMP results are successful or not. The intended host, on netwatch, can be addressed to a Public IP or Local IP, for example a certain server. On netwatch there are UP and DOWN parameters that can be used to execute predefined scripts/information. if the check is successful, the script/information contained in the UP will be executed. Meanwhile, if the check fails, it means that the connection is broken, then the script on DOWN will be executed. So that periodically an administrator can easily monitor internet access used to make sure everything is running or UP.